Identification of Autophagy-Associated Biomarkers and Corresponding Regulatory Factors in the Progression of Colorectal Cancer - Zhang, Chunrui; Jiang, Jing; Wang, Liqiang; Zheng, Liyu; Xu, Jiankai; Qi, Xiaolin; Huang, Huiying; Lu, Jianping; Li, Kongning; Wang, Hong (Frontiers in Genetics, 2020)
The text has a total of 3182 words Abstract Autophagy is a self-degradation process that maintains homeostasis against stress in cells. Autophagy dysfunction plays a central role in the development of tumors, such as colorectal cancer. In this study, autophagy-related differentially expressed genes, their downstream functions, and upstream regulatory factors including RNA-binding proteins (RBP) involved in programmed cell death in the colorectal cancer were investigated. Transcription factors and miRNAs have been shown to mainly regulate autophagy genes. Interesting, we found that some of the RNA-binding proteins in the colorectal cancer, such as DDX17, SETDB1 and POLR3A, play an important regulatory role in maintaining autophagy at a basal level during growth by acting as transcription factors that regulate autophagy. Promoter methylations showed negative regulations on differentially expressed autophagy gene (DEAG), while copy number 2 variations revealed a positive role in them. A proportional hazards regression analysis indicated that using autophagy-related prognostic signature can divide patients into high-risk and low-risk groups. Autophagy associated FDA-approved drugs were studied by a prognostic network. This would contribute to identifications of new potential molecular therapeutic targets for colorectal cancer.